Hypermobility in women with fibromyalgia syndrome - GÜNDÜZ, OSMAN HAKAN (SPRINGER LONDON LTD, 2006)
The purpose of this study was to evaluate the relationship between hypermobility and fibromyalgia syndrome (FS) in women. Ninety-three women with FS who met the American College of Rheumatology criteria for FS and 58 healthy women without FS were included in this study. All women were examined for hypermobility by blinded observers using the Beighton criteria. The mean age was 43.5 +/- 9.9 (21-68) and 40.2 +/- 11.1 (21-63) years in the FS and control groups, respectively, and the two groups were statistically similar (p > 0.05). The mean Beighton total score was 4.7 +/- 2.1 and 2.9 +/- 2.4 in the FS and control groups, respectively (p < 0.0001). The frequency of joint hypermobility was 64.2% in the FS group and 22% in the control group. In accordance with the Beighton criteria (p < 0.05), we found that the joint hypermobility ratio was significantly higher in patients with FS than in subjects without FS. Additionally, we evaluated the correlation between the total Beighton score and the age and number of trigger points. There were negative correlations between the total Beighton score and the age (r=-0.42, p < 0.001) and number of trigger points (r=-0.24, p=0.03) in all patients. Hypermobility syndrome is more common in women with FS than in those in the control group. Therefore, the relationship between hypermobility and FS should be taken into consideration in the diagnosis and follow-up of women, especially those with widespread pain.
Keywords: Beighton criteria; fibromyalgia; hypermobility; musculoskeletal pain; JOINT HYPERMOBILITY